Electrohydrodynamically Printed Microlens Arrays with the High Filling Factor near 90% - Linkun Zhong; Weixuan Liu; Hongbo Gong; Ye Li; Xueqian Zhao; Delai Kong; Qingguo Du; Bing Xu; Xiaoli Zhang; Yan Jun Liu (Photonics)
Microlens arrays (MLAs) are essential for light collection, extraction, and high-resolution imaging. However, most reported MLAs have a limited filling factor. Here, we demonstrate MLAs using three different UV-curing optical adhesives based on the electrohydrodynamic inkjet (E-jet) printing technique. The highest filling factor of 89.91% is achieved. By controlling the curvature of the microlens via the surface treatment of the substrate, a series of MLAs with different numerical apertures can be obtained. With the high-consistency printing technique, the demonstrated high filling factor MLAs could be potentially useful to improve the performance of optical imaging and sensing systems.